(untitled) (Research, Society and Development, 2020)
The aim of the present study was to analyze the literature on the use of phytotherapeutc drugs in dentistry. It is an integrative review of the literature that used the descriptors: dental surgeon, ethnopharmacology, phytotherapeutic drugs, separately and later crossing them through the Boolean operator AND. The databases consulted were Scientific Electronic Library Online (SciELO) and Medical Literature Analysis and Retrievel System online (MEDLINE). Thirteen indexed articles were analyzed. The results show that herbal medicines have gained space in the dental sector, mainly after the approval of the National Policy of Integrative and Complementary Practices (PNPIC) in SUS and the Federal Council of Dentistry, and even with scientific evidence of the pharmacological effectiveness of this therapy, there is a resistance to the indication and prescription of herbal medicines by some dentists, justified most of the time by lack of technical knowledge of this therapy. The use of this practice by the dentist has been carried out mainly in metropolises, with an emphasis on the southern region of Brazil, and even though some professionals claim not to practice herbal medicine due to technical ignorance, it is clear that it has been widely used by professionals working in the Strategy of Family Health